THE IMPACT OF DEPRIVATION ON THE FORMATION OF A CHILD'S PERSONALITY: PSYCHOLOGICAL ASPECTS AND CONSEQUENCES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Formation and development of a healthy generation is connected not only with physical development, but also with harmonious psychological development of the personality. Psychological counselling to the present day shows a number of urgent problems related to the psychological development of children. Among them are problems of relationships between parents and children, inability to communicate constructively and solve problems between parents and children, etc. The consequence of this is that a great number of children grow up in conditions of deficiency of contact with adults, emotional acceptance and empathy, information about the surrounding world, various emotional and mental stimulation, etc. Failure to meet needs of this kind contributes to the emergence of mental deprivation. Mental deprivation in childhood leads to distortion of the process of development and formation of the child's personality, which is manifested in difficulty in establishing contacts with others and reduced ability to social adaptation, as well as in mental retardation. This article will examine how different types of deprivation (emotional, social, sensory) affect the development and formation of a child's personality. Key factors that promote or hinder healthy psycho-emotional development will be analysed, and recommendations for parents and professionals in working with children who have experienced deprivation will be offered.